Magnetotelluric 1D-Based Lithological Study of Geothermal Prospect Near Bogor Fault, Kepahiang - Zaky Muammar; M Farid; Arif Ismul Hadi; Andre Rahmat Al-Ansory; Hana Raihana (Department of Physics Education, Universitas Mataram, 2026)
Kepahiang Regency, Bengkulu Province has significant geothermal potential due to its location on the subduction line and the Sumatra Musi segment fault. This research aims to identify the subsurface lithology of the geothermal zone using the Magnetotelluric method. This method measures the response of natural electric and magnetic fields to determine subsurface resistivity values. Inversion of 1D Magnetotelluric data at six pointsv (MT5, MT6, A6, A5, A1, A4) showed three classes of resistivity values of low (0.21-4.0 Ωm), medium (31-80 Ωm), and high (≥200 Ωm). Low resistivity zones are found at MT6 and A6, indicating the presence of geothermal reservoirs in the form of sandstone, limestone, and igneous rocks. Medium resistivity at MT5 and A5 indicates a clay layer as caprock, while high resistivity at A1 and A4 indicates hot rocks in the form of granite and metamorphic rocks. These results provide a preliminary picture of geological conditions for geothermal exploration in the area.